2018
DOI: 10.35868/1997-3004.28.33-40
|View full text |Cite
|
Sign up to set email alerts
|

Production of Phytohormones of Bradyrhizobium Japonicum and Azospirillum Brasilense Under Their Simultaneous Cultivation

Abstract: Objective. Investigate the activity of biosynthesis of phytohormonal substances with nitrogen-fixing bacteria Bradyrhizobium japonicum and Azospirillum brasilense in pure and mixed culture. Methods. Microbiological, chromatographic, and mathematical. Results It has been established that the simultaneous cultivation of B. japonicum M-8 and A. brasilense 410 increases the content of gibberellins and cytokinins in the culture fluid of the test microorganisms. The content of gibberellic acid and isopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some studies have shown that nodule bacteria of legumes in pure culture can produce auxins, cytokinins, gibberellins, and other phytohormonal substances [6,7]. Here is information about direct lines correlations between symbiotic activity and the ability of bacteria to actively synthesize cytokinins [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that nodule bacteria of legumes in pure culture can produce auxins, cytokinins, gibberellins, and other phytohormonal substances [6,7]. Here is information about direct lines correlations between symbiotic activity and the ability of bacteria to actively synthesize cytokinins [8].…”
mentioning
confidence: 99%
“…It is known that rhizobia strains are capable of synthesizing extracellular cytokinins involved in the regulation of cell division processes, which initiates the formation of root nodules [1][2][3][4][5][6][7][8]20].…”
mentioning
confidence: 99%